Salik Buta: Aliran Tasawuf Aceh Abad XX - Misri A Muchsin (Al-Jami'ah Research Centre, 2004)
This article examines the Sufi movement in Aceh by looking at its continuity since the 16th -17th century, as its golden age, to the 20th century. Based on the fact that Abdullah Ujong Rimba's explanation is considered representative, his books are taken as primary sources while others are secondary. Based on Abdullah Ujong Rimba's explanation, Salik Buta is a sect of Sufism in Aceh in the 20th century. This sect is practiced in several of center in Aceh. Historically, the doctrine of this sects is continuation and modification of Wahḍat al-Wujūd's doctrines established since 16th century. The doctrine of Salik Buta are different from those of popular Sufism. Thus, Salik Buta is considered heterodox and criticized by ulama, as Abdullah Ujong Rimba. From Abdullah Ujong RImba's criticism, it can be conclude that his thought based on syari'at or Fiqih orientation, instead of the perspective of Sufism.